Analisis Kualitas Produk Donat untuk Meningkatkan Keuntungan Menggunakan Metode Quality Function Deployment (QFD) - Sekar Arum Choirunisa; Suntoro Suntoro; Wahyudi Adiprasetyo (Journal of Innovative and Creativity, 2025)
The culinary industry is one of the rapidly growing MSME sectors, as food is a primary necessity that is constantly in demand. Donuts are among the most popular snack products, favored for their soft texture, delicious taste, and attractive topping variations. However, the high consumer interest also creates intense business competition, with many new entrepreneurs offering innovative flavors and diverse marketing strategies. This condition requires MSMEs to maintain product quality while adapting to consumer needs and preferences. UMKM X, a donut producer established in Bandung since 2008, faces this challenge despite having a relatively large production capacity. On average, 7,200 donuts remain unsold each month, posing potential losses since donuts have only a one-day shelf life, leading to product waste or discounted sales. This study applies the Quality Function Deployment (QFD) method with the House of Quality (HOQ) analysis tool to identify customer needs and benefits, measure levels of importance and satisfaction, and map out product attributes that require improvement based on their relationship to technical characteristics. The findings indicate that the most important attributes for consumers are soft and fluffy donut texture (average score 4.78), good taste (4.71), and friendly service (4.64). Meanwhile, the highest satisfaction level is affordability across consumer groups (4.15), while the lowest is topping or filling variations that are not overly sweet (3.1). Based on these results, priority improvements for UMKM X include enhancing topping variety, improving donut texture, and strengthening taste quality to maintain customer satisfaction and achieve greater profitability.